THE ROLE OF INFORMATION TECHNOLOGY (IT) IN KNOWLEDGE MANAGEMENT PROCESS AT BUSINESS ADMINISTRATION DEPARTMENT LECTURERS, STATE POLYTECHNIC OF MALANG - Asminah Rachmi; Tri Istining Wardani; Kartika DS Susilowati (Jurnal Akuntansi Bisnis dan Humaniora, 2021)
The role of universities in providing knowledge and learning in various scientific disciplines has positioned universities as knowledge-based organizations. This suggests that universities have an important level of knowledge management (KM) activity although they may not have formal KM practices. This study aims to investigate the knowledge management process with its various dimensions namely knowledge creation, acquisition, organization, sharing and implementation in the Business Administration Department State Polytechnic of Malang. It also to identify the use of IT (hardware, software, security and usability) including the impotance of IT in supporting KM process to increase the competitiveness of Business Administration Department, Malang State Polytechnic. This research is qualitative research using case study approach. The research subject is Business Administration Department, State Polytechnic of Malang. Unit analyses are head of Department, secretary of department, head of study program, lecturers and administratif staffs. Data collection methods use interview, observation, and document analysis. Data analysis use within case analysis. The research findings showed that activities held by the Business Administration Department are in accordance with a knowledge management system such as capture, store, change and share knowledge from the department to other members of the organization. The IT components including hardware, software, intranet, and internet networks as well as integrated applications facilitate all the activities. Suggestions were provided related to updating IT that should be conducted regularly including increasing internet network capacity to support knowledge management process that will increase organization performance.